Joaquim Tomás Lobo d'Ávila, conde de Valbom - Pereira, Hugo Silveira (2018)
The Regeneração was characterized by the careers of several men of science and technology, who sought to apply the scientific and technological concepts they had learned in European schools to the modernization of Portugal. Amongst this elite, we find the name of Joaquim Tomás Lobo d'Ávila, earl of Valbom. In this paper we will draw this engineer's biographical sketch, using the scientific persona concept. We will use a diverse array of sources that will allow us to follow his career as a politician and diplomat, but mainly as a technocratic engineer. We aim to show the relevance of Lobo d'Ávila individual history in the development strategy followed in Portugal in the second half of the 19th century. Also, in a double perspective, we aim to analyse the importance of his individual history in the formation of the technocratic persona and the relevance of this persona in his own trajectory.